Saint Vincent and the Grenadines. Significant achievements 2015 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2022)
The main activities carried out by the Institute in Saint Vincent and the Grenadines during 2015 are identified, with respect to the needs and interests of the country, strengthening issues such as family farming, competitiveness, trade, soil management, rainwater harvesting, forest management and resilience against climate change. Finally, marketing, pork and sweet potato production were supported.